2012
DOI: 10.1159/000342917
|View full text |Cite
|
Sign up to set email alerts
|

Well-Differentiated Villoglandular Adenocarcinoma of the Uterine Cervix: Assessment of Cytological Features by Histological Subtypes

Abstract: Objective: Well-differentiated villoglandular adenocarcinoma (VGA) of the cervix involves papillae lined by different types of epithelial cells that are histologically subclassified into endocervical, endometrioid, or intestinal subtypes. The objective of the current study was to evaluate the definite cytological features of VGA by histological subtype. Study Design: We examined 8 cervical smears from patients confirmed to have pure VGA and classified them into the 3 histological subtypes. Results: The cervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…However, Young and Scully (2) reported that only 1 out of 13 patients with VGPA had a history of oral contraceptive use. Giordano et al (1) and Hagiwara et al (6) reported that no patient had taken oral contraceptives prior to diagnosis. In the present cases, all 4 patients denied a history of oral contraceptive use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, Young and Scully (2) reported that only 1 out of 13 patients with VGPA had a history of oral contraceptive use. Giordano et al (1) and Hagiwara et al (6) reported that no patient had taken oral contraceptives prior to diagnosis. In the present cases, all 4 patients denied a history of oral contraceptive use.…”
Section: Discussionmentioning
confidence: 99%
“…The disease was described for the first time by Young and Scully (2) in 1989, and predominantly affects young women (2)(3)(4)(5)(6)(7). Based on its infrequent lymphovascular space invasion and lymph node metastasis, VGPA is generally considered to have relatively indolent behavior and an excellent prognosis compared with other types of cervical adenocarcinomas (2)(3)(4)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It therefore has a more favorable outcome than the usual endocervical type, and in this younger population more likely to desire fertility, can be managed conservatively via cone excision only, if all of the above criteria are met, no conventional adenocarcinoma is present, and if the margins are free of disease, and no lymphovascular invasion is identified. Cytologically, villoglandular adenocarcinoma presents as dense three-dimensional groups, often with bulbous projections 21 (Figure 12). Mucinous adenocarcinoma is also uncommon but has more frequently been reported in the Japanese population (up to 25% of endocervical adenocarcinoma).…”
Section: Invasive Endocervical Adenocarcinomamentioning
confidence: 99%